NGHIÊN CỨU CHẾ TẠO SƠN PHỦ BẢO VỆ TẠM THỜI BỀ MẶT CÁC CHI TIẾT KIM LOẠI - Nguyễn, Văn Vinh; Hà, Hữu Sơn; Lê, Quốc Phẩm (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH ON MANUFACTURING THE PAINT COATING USED FOR TEMPORARY PROTECTION OF METAL SURFACESThis article presents the results of research on manufacturing the paint coating from the raw materials available in domestic market. The paint coating is intended to be used for temporary protection of metal surfaces. The raw materials include copolymer resin of vinyl chloride and vinyl acetate, dibutyl phthalate plasticizer and solvent mixture of toluene and methyl ethyl ketone. The paint coatings made from different mixture formulas of the raw materials were tested to find out the optimal one M2, based on which the prepared coating was easiest to be totally pulled off from metal surface. Also, the coating from M2 formula was tested to assess other physical-chemical properties in comparison with that of the paint coating XC-567 imported from Russia. Additionally, the accelerated test was carried out as well to compare the pull off ability of the two paint coatings. The test result showed that the quality of the coating based on M2 formula was equivalent to that of paint coating XC-567 made in Russia.